Graphene oxide-enhanced alginate-PVA biopolymer electrolytes with improved proton conductivity and electrochemical stability for supercapacitor applications - Nurfatin Nabilah, Abdul Hafidz; Nuraziliana, Muhd Ghazali; Norfatihah, Mazuki; Diantoro, M.; Nagao, Yuki; Ahmad Salihin, Samsudin (Elsevier Ltd, 2025)
This study explores the effect of graphene oxide (GO) incorporation on the structural and electrochemical properties of alginate–poly(vinyl alcohol) (PVA) polymer electrolytes doped with ammonium nitrate (NH₄NO₃) for supercapacitor applications. FTIR analysis revealed specific molecular interactions between graphene oxide (GO) and the polymer host, while XRD results confirmed the enhanced amorphous nature of the composite. At 2 wt.% GO loading, the system exhibited peak ionic conductivity of 1.07 × 10-3 S/cm at room temperature, with a high ionic transference number (tₙ ≈ 0.98) and an extended electrochemical stability window of 2.85 V. Symmetric supercapacitors fabricated with these electrolytes achieved a specific capacitance of 240.78 F/g, an energy density of 131 Wh /kg, and long-term cycling stability up to 10,000 cycles. These results demonstrate that GO-induced structural modulation significantly enhances proton transport and electrochemical performance, offering a promising biopolymer-based platform for next-generation energy storage devices.